Information use in design - Van Epps, Amy S. (Qualitative and Quantitative Methods in Libraries; Vol 7 No 2 (2018): June 2018 Issue, 2019)
Librarians are regularly working to understand how students make decisions around information use to inform the development of more relevant learning activities. The more relevant the activities when students are learning any new skill, the more likely they are to understand the task and incorporate the learning into future design decisions and writing. The need to build connections and understanding is critical in adoption of information literacy. In this study, the researcher analyzed the transcript from an end of semester focus group with students in a design class about their information use during the semester project. The transcript was analyzed using deductive thematic analysis while simultaneously staying open to emergent codes.